Kinetic and Isotherm Studies of Nitrate Adsorption in Salt Water Using Modified Zeolite - Kuntari Kuntari (Bulletin of Chemical Reaction Engineering & Catalysis, 2021)
Nitrate is the main form of nitrogen species in natural waters. Excessive nitrate concentration in water is highly undesirable, so that removal of the excessive nitrates in waters is very important. However, the challenge is purposed to remove the excessive nitrates in sea waters by considering anions-rich sea water. Adsorption is a favorable method for the nitrate removal process. Therefore, this research was aimed to study the kinetics and isotherm of nitrates adsorption in salt water. The adsorbent preparation was done by modifying natural zeolite with iron oxide. The adsorbent characterization was carried out by FT-IR spectroscopy and Gas Sorption Analyis methods. The results showed that the modified zeolite have Fe−O group vibrations as indicated by a peak at a wave number of 1404.18 cm−1 and an increased specific surface area. The modified zeolite is capable of adsorbing nitrate ions. The adsorption isotherms studies indicated that the modified zeolite is appropriate to the Dubinin-Radushkevich model. The average adsorption energy value (ED), obtained based on the Dubinin-Radushkevich isotherm <2 kJ/mole, showed that the nitrate adsorption on zeolite surface occurred physically. The most suitable adsorption kinetics model is the pseudo second order with the rate constant of 1.80´10−2 g/mg.min. Copyright © 2021 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).